EDUKASI KESEHATAN DENGAN PENGGUNAAN METODE AUDIOVISUAL TENTANG STUNTING PADA KELUARGA DENGAN BALITA DI PUSKESMAS WILAYAH KERJA CIHERANG KABUPATEN CIANJUR TAHUN 2023 - Hartati, Sri; Patimah, Papat; Widianti, Rina Andriana; Kurniawati , Stefani Chairunisa; Umaemah, Siti (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2023)
This research aims to find out Health Education with the Use of Audiovisual Methods on Stunting in Families with Toddlers 2023. The method used is Audio Visual and active discussion on families with toddlers 20 people. Data on knowledge about stunting was collected using pretest and posttest questionnaires. Results: The results obtained at the time of pretest respondents with good knowledge were 50%, sufficient knowledge were 30%, and less knowledge were 20%. At the time of the posttest, 80% of respondents with good knowledge, 20% with sufficient knowledge and 0% with insufficient knowledge. Conclusion: Health education with the use of audiovisual methods can improve the knowledge of families with toddlers about stunting 2023. Future research needs to consider further monitoring and evaluation at a certain period of time to see the memory ability and attitude of mothers who have stunted children.